Implementasi Sistem Manajemen Mutu Iso 29993:2017 pada Klausul Fasilitator di Program Pelatihan Perdagangan Ekspor LPK Global Edukasi Talenta Inkubator - Nurul Elfiana; Robiatul Adawiyah; Hamzah Robbani (Neolectura, 2023)
The first problem is the lack of compliance with the Quality Management System ISO 29993:2017 which should be a reference for facilitators in carrying out the learning process in job training institutions. The second problem is that there is no identification of improvement efforts that must be carried out by job training institutions in order to achieve the goals of the institution's vision and mission. The purpose of this study was to find out how LPK Global Talent Education Incubator's efforts in implementing ISO 29993:2017 in the facilitator clause in the export trade training program. This study uses a qualitative method with a case study approach. Qualitative research with a case study approach is intended to study in depth the background of the situation and the current position which is what it is. The research stages included: Research, Observation and in-depth interviews. This research used a population of 3 management, facilitators and alumni training participants. The sampling technique is a saturated sample, namely 3 people. The data collection stage consists of observation techniques and interview techniques. The steps taken in the data checking stage were carried out after interviews and observations. The method of analysis for this research is observation and interviews from the data. The results of the research and analysis with data processing show that the Global Talent Education Incubator Education Institute has implemented the existing quality management system, but something must still be evaluated in running the quality management system. The author's suggestion is that in carrying out the learning process the facilitator should better prepare himself both methodologically and technically adapted to the learning environment and pay more attention to the basic requirements of the facilitator and the learning process so that nothing is missed regarding the existing quality management.